Karyomegalic Interstitial Nephritis: A Case Report and Review of the Literature. Issue 20 (May 2016) - Isnard, Pierre; Rabant, Marion; Labaye, Jacques; Antignac, Corinne; Knebelmann, Bertrand; Zaidan, Mohamad
Abstract : Abstract: Karyomegalic interstitial nephritis is a rare cause of hereditary chronic interstitial nephritis, described for the first time over 40 years ago. A 36-year-old woman, of Turkish origin, presented with chronic kidney disease and high blood pressure. She had a history of recurrent upper respiratory tract infections but no familial history of nephropathy. Physical examination was unremarkable. Laboratory tests showed serum creatinine at 2.3 mg/dL with an estimated glomerular filtration rate of 26 mL/min/1.73m 2, and gamma-glutamyl transpeptidase and alkaline phosphatase at 3 and 1.5 times the upper normal limit. Urinalysis showed 0.8 g/day of nonselective proteinuria, microscopic hematuria, and aseptic leukocyturia. Immunological tests and tests for human immunodeficiency and hepatitis B and C viruses were negative. Complement level and serum proteins electrophoresis were normal. Analysis of the renal biopsy showed severe interstitial fibrosis and tubular atrophy. Numerous tubular cells had nuclear enlargement with irregular outlines, hyperchromatic aspect, and prominent nucleoli. These findings were highly suggestive of karyomegalic interstitial nephritis, which was further confirmed by exome sequencing of FAN1 gene showing an identified homozygous frameshift mutation due to a one-base-pair deletion in exon 12 (c.2616delA). The present case illustrates a rare but severe cause of hereditary interstitial nephritis, sometimes accompanied by subtle extrarenal manifestations. Identification of mutations in FAN1 gene underscores recent insights linking inadequate DNA repair and susceptibility to chronic kidney disease.